Impact of Risk Factors on the Size of Ruptured Intracranial Saccular Aneurysms - Kabir Sarker, Md Humayun; habib, Monsur; Md Shahidullah, -; Kanti Dey, Shuvash; Islam, shafiqul; Islam, Md Rafiqul; Ahmed, Kazi Gias Uddin; Shahaly, S; Imran, MS; Hasan, M (Bangladesh Journal of Neuroscience, 2019)
Background: Un-ruptured intracranial aneurysms (UIAs) are common and prevalence is about 2 to 8%. Several studies have shown that the decision to treat un-ruptured aneurysms should not be based on aneurysm size alone. A study suggest that treatment of UIAs smaller than 7 mm in hypertensive patients and smokers may be beneûcial. Aim and objective: The goal of this study is analysis of correlation of age, gender, location of the aneurysm, history of hypertension and cigarette smoking, previous history of SAH with the size of ruptured aneurysms. Materials and Methods: This hospital based observational cross-sectional study was conducted in the Department of Neurology & Neurosurgery, Dhaka Medical College Hospital (DMCH), Dhaka. Total 44 patients with SAH were taken by inclusion & exclusion criteria. The aneurysms size, site of location and aneurysm multiplicity was assessed by three-dimensional rotational digital subtraction angiography (DSA). Results:The mean age of the study population was 49.24 ±11.5. About half of the population were within 51-60 years. The male female ratio was 1:1.2. Out of 44 population, 93.2% were presented with headache, 90.9% with vomiting. In this study aneurysms mean size was 5.72±4.010 mm. 93.2% of aneurysms were below 10 mm, 75.0% were below 7 mm and 50.0% below 5 mm. Size of ruptured aneurysm is small in hypertensive population and is significant (p-value 0.037). Aneurysm size was significantly (p- value 0.013) smaller in case of smoker. Mean aneurysm size in hypertensive smoker population was significantly (p-value-0.004) smaller than hypertensive non-smoker. Population with one risk factor had mean aneurysm size was 8.32±6.84 mm, two risk factors had 5.26±1.86mm, three risk factors had 4.79±2.05 mm and more than three risk factors had 2.85±1.43. Conclusion: This study shows that more the risk factors, smaller the size of aneurysms. Therefore, history of hypertension, cigarette smoking, female sex, age and positive family history should be considered in the assessment of treatment of un-ruptured intracranial aneurysms. Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 86-94